Pelatihan Pengelolaan Keuangan dan Strategi Pemasaran Digital bagi Pengrajin Kemplang di Desa Pelabuhan Dalam Kabupaten Ogan Ilir - Budiman, Muhammad Akbar; Riswan Jaenudin; Agung Putra Raneo; Nafilah Khoirunnisa; Try Darma Agustiawan (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance the capacity of kemplang artisans in financial management and digital marketing strategies through the use of social media and online marketplaces. The implementation methods included socialization, training, technology application, mentoring, and evaluation. The innovations introduced involved the use of templates from the Simple Accounting Module and the utilization of Shopee, Facebook, and TikTok for digital marketing. The evaluation employed observation instruments and assessment guidelines analyzed using descriptive quantitative methods. The results show improvement in both aspects: 80% of participants achieved a Good to Very Good category in financial management skills, including the accuracy of transaction recording and preparation of simple financial reports. Meanwhile, in the digital marketing aspect, 80.95% of participants also reached the Good to Very Good category in promotional content creation, advertisement visual quality, and the construction of effective messages on social media and marketplace platforms. These findings indicate that this community service activity effectively contributes to strengthening local economic independence by enhancing the managerial and digital capacities of kemplang artisans.